2006
DOI: 10.1111/j.1600-0714.2006.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of hepatitis C virus infection in Serbian patients with oral leukoplakia

Abstract: The present data indicate that patients with OL resident in Serbia do not have evidence of HCV or HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Thus, the prevalence of leukoplakia in our study seems to reflect the oral habits of tobacco consumption in the studied group and possibly does not represent a real association with hepatitis C infection. This observation is in accordance with research from Bokor‐Bratic (42) on Serbian patients.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the prevalence of leukoplakia in our study seems to reflect the oral habits of tobacco consumption in the studied group and possibly does not represent a real association with hepatitis C infection. This observation is in accordance with research from Bokor‐Bratic (42) on Serbian patients.…”
Section: Discussionsupporting
confidence: 93%
“…Their finding suggests that HBV infection is unlikely to play a major role in oral tumor formation. A study by Bokor-Bratic also suggested that oral leukoplakia was not associated with HBV infection in Serbia [37]. In addition, only HCV has the lymphatrophic character that is assumed to be the cause of HCV-associated extrahepatic manifestations [38].…”
Section: Discussionmentioning
confidence: 98%
“…However, HCV is a common cause of liver cirrhosis which may represent itself an independent risk factor for the development of oral cancer (Sorensen et al , 1998). On the other hand, potentially oral premalignant lesions such as leukoplakia and oral epithelial dysplasia are not associated with HCV infection (Carrozzo et al , 1996; Jaber et al , 2003; Bokor‐Bratic,2006).…”
Section: Oral Carcinomamentioning
confidence: 99%